L1CAM and HER2 Expression in Early Endometrioid Uterine Cancer. (July 2017) - Abdel Azim, Samira; Sprung, Susanne; Mutz-Dehbalaie, Irene; Fessler, Siegfried; Zeimet, Alain G.; Marth, Christian
Abstract : Recently L1CAM was shown to be a promising biomarker for early-stage endometrial carcinoma (EC). As L1CAM expression was found to be related to serous ECs and areas of serous differentiation in endometrioid carcinomas, there is evidence that L1CAM-positive cancers more likely resemble type II carcinomas. Furthermore, expression of growth factor receptor HER2 has been found to be closely associated with serous ECs. We conducted a retrospective study on 142 patients in FIGO stages I and II with endometrioid EC and analyzed L1CAM and HER2 expression by double-staining immunohistochemistry. The association between these 2 transmembrane molecules and their impact on patient outcome was analyzed. Both L1CAM and HER2 showed a significant association with recurrent disease ( P <0.001 and P =0.007, respectively). We found 39 (27%) L1CAM-positive cases and 17 (12%) HER2-positive cases. About 6.3% of cases were positive for both biomarkers. Survival of L1CAM-positive patients showed a significant difference between HER2-positive and HER2-negative patients ( P =0.019) regarding disease-free survival. The most unfavorable disease-free survival and overall survival was found for patients with L1CAM and HER2 double-positive tumors ( P <0.001). Double immunostaining revealed a mutually exclusive staining pattern for L1CAM and HER2 expression on the level of tumor cells. In early endometrioid uterine carcinoma, an additional expression of HER2 to L1CAM seems to further worsen disease-free survival and overall survival. In terms of "personalized medicine, " detection of these molecules in endometrioid ECs may open new avenues for targeted therapies with the newly available anti-HER2 drugs and/or with the upcoming humanized anti-L1CAM antibodies.